A severe and irreversible case of tardive rigid-akinetic parkinsonian syndrome: the role of the DaTscan - Politis, A. M.; Kokras, N; Pappa, D.; Siarkos, C.; Katirtzoglou, E.; Papadimitriou, G.N.; Kahn, D. A. (J Psychiatr Pract, 2013)
In elderly patients, exposure to antipsychotic medication and subsequent withdrawal may lead to the development of persistent extrapyramidal symptoms, possibly including a syndrome suggested to be tardive parkinsonism. We describe a case in which withdrawal of antipsychotics was unexpectedly associated with progressive deterioration, rather than improvement, of extrapyramidal parkinsonian symptoms. Abnormal imaging of presynaptic dopamine transporters (DaTs) using single-photon emission computed tomography (SPECT) with ioflupane I 123 (DaTscan) substantially contributed to the differential diagnosis, suggesting it was likely that the patient had an underlying neurodegenerative disorder that preceded the onset of medicationinduced parkinsonian symptoms. Our report illustrates how novel findings from DaTscan may assist with diagnosing the cause of persistent parkinsonian symptoms after antipsychotic withdrawal and provide insight into the controversial concept of tardive parkinsonism.
Keywords: Aged, 80 and over; Antipsychotic Agents/adverse effects; Brain/diagnostic imaging; Diagnosis, Differential; Dopamine Plasma Membrane Transport Proteins/metabolism; Female; Haloperidol/adverse effects; Humans; Iodine Radioisotopes; Lewy Body Disease/diagnosis/diagnostic imaging; Neuroimaging/methods; Nortropanes; Parkinson Disease, Secondary/*chemically induced/diagnosis/diagnostic imaging; Tomography, Emission-Computed, Single-Photon/*methods